2023
DOI: 10.1037/cns0000227
|View full text |Cite
|
Sign up to set email alerts
|

Combining presleep cognitive training and REM-sleep stimulation in a laboratory morning nap for lucid dream induction.

Abstract: Previous experiments combining cognitive techniques and sleep disruption have been relatively successful in inducing at-home lucid dreams over training periods of 1-week or more. Here, we induce lucid dreams in a single laboratory nap session by pairing cognitive training with external stimulation. Participants came to the laboratory at 7:30 am or 11:00 am and during polysomnography setup were provided with information about lucid dreaming. For twenty minutes prior to sleep the experimenter played alternating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 59 publications
3
47
0
1
Order By: Relevance
“…Our questionnaire measures showed that in fact nightmare participants scored higher on the Highly Sensitive Person Scale. This is in line with a prior finding that nightmare sufferers are more highly sensitive than control subjects ( Carr et al, 2020 ), providing further support to the notion that sensory-processing sensitivity is a trait marker for nightmares.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our questionnaire measures showed that in fact nightmare participants scored higher on the Highly Sensitive Person Scale. This is in line with a prior finding that nightmare sufferers are more highly sensitive than control subjects ( Carr et al, 2020 ), providing further support to the notion that sensory-processing sensitivity is a trait marker for nightmares.…”
Section: Discussionsupporting
confidence: 91%
“…Our questionnaire measures showed that in fact nightmare participants scored higher on the Highly Sensitive Person Scale. This is in line with a prior finding that nightmare sufferers are more highly sensitive than control subjects (Carr et al, 2020), providing further support to the notion that sensory-processing sensitivity is a trait marker for nightmares. Analysis of the dream diary ratings showed that nightmare sufferers exhibit significantly more negative emotional intensity, negative body sensations, and distress from their dreams than did control subjects, although the two groups did not differ in the amount of positive emotion, sensations or impact of their dreams.…”
Section: Discussionsupporting
confidence: 90%
“…Two recent sleep laboratory studies applying an acoustic cue during the induction technique of the WBTB-paradigm might shed some light on the timing issue. In the first study lucid dreams were successfully induced in a single nap session by cueing beeping tones with cognitive training (Carr et al, 2020). The session duration was 20 min and performed in the morning either at 7:30 am or 11:00 am.…”
Section: Discussionmentioning
confidence: 99%
“…Similar sense making is evident in studies of lucid dreams, where audio or visual stimuli become contextualized in the dream environment ( LaBerge & Levitan, 1995 ). For instance, when presented with flashing LED lights one lucid dreamer reports, “I could tell when the red light came on because it got hot and the sun got brighter” ( Carr, Konkoly, Mallett, Edwards, Appel, & Blagrove, 2020 ). In another example, an audio cue was contextualized in the following dream: “I was shopping in a supermarket… I could hear the beeping and it was like I was getting loads of messages on my phone telling me what to buy … things like, ‘buy some biscuits’.…”
Section: Introductionmentioning
confidence: 99%
“…via DreamLight mask, LaBerge & Levitan, 1995 ). Within a Targeted Lucidity Reactivation (TLR) protocol, audio and visual stimuli are associated with a lucid mind-state prior to sleep, and then re-presented during REM sleep; this technique induced lucid dreams in 50% of participants in a morning nap ( Carr et al, 2020 ). In addition, novel protocols are emerging all the time; for instance, Targeted Dream Incubation creatively combines components of targeted reactivation with intentional incubation at the hypnagogic border between sleep and wake ( Horowitz, Cunningham, Maes, & Stickgold, 2020 ).…”
Section: Introductionmentioning
confidence: 99%